Insertions and Duplications in the Polyproline Region of the Hepatitis E Virus - Lhomme, Sébastien; Nicot, Florence; Jeanne, Nicolas; Dimeglio, Chloé; Roulet, Alain; Lefebvre, Caroline; Carcenac, Romain; Manno, Maxime; Dubois, Martine; Peron, Jean-Marie; Alric, Laurent; Kamar, Nassim; et al. (Frontiers in Microbiology, 2020)
Recombinant strains of hepatitis E virus (HEV) with insertions of human genomic fragments or HEV sequence duplications in the sequence encoding the polyproline region (PPR) were previously described in chronically infected patients. Such genomic rearrangements confer a replicative advantage in vitro but little is known about their frequency, location or origin. As the sequences of only a few virus genomes are available, we analyzed the complete genomes of 114 HEV genotype 3 strains using the single molecular real-time sequencing method to determine the frequency, location and origin of inserted genomic fragments, plus the proportions of variants with genomic rearrangements in each virus quasispecies. We also examined the amino acid compositions and post-translational modifications conferred by these rearrangements by comparing them to sequences without human gene insertions or HEV gene duplications. We found genomic rearrangements in 7/114 (6.1%) complete genome sequences (4 HEV-3f, 1 HEV-3e, 1 HEV-3h and 1 HEV-3chi-new), all from immunocompromised patients, and 3/7 were found at the acute phase of infection. Six of the 7 patients harbored virus-host recombinant variants, including 1 patient with 2 different recombinant variants. We also sequenced 3 recombinant variants with genome duplications of the PPR or PPR+X domains in a single patient. All the genomic rearrangements (7 human fragment insertions of varying origins and 3 HEV genome duplications) occurred in the PPR. The sequences with genomic rearrangements had specific characteristics: increased net load (p<0.001) and more ubiquitination (p<0.001), phosphorylation (p<0.001) and acetylation (p<0.001) sites. The human fragment insertions and HEV genome duplications had slightly different characteristics. We believe this is the first description of HEV strains with genomic rearrangements in patients at the acute phase of infection; perhaps these strains are directly transmitted. Clearly, genomic rearrangements produce a greater net load with duplications and insertions having different features. Further studies are needed to clarify the mechanisms by which such modifications influence HEV replication.